Poldip2 controls leukocyte infiltration into the ischemic brain by regulating focal adhesion kinase-mediated VCAM-1 induction - Lori N. Eidson (Nature Portfolio, 2021)
Abstract Stroke is a multiphasic process involving a direct ischemic brain injury which is then exacerbated by the influx of immune cells into the brain tissue. Activation of brain endothelial cells leads to the expression of adhesion molecules such vascular cell adhesion molecule 1 (VCAM-1) on endothelial cells, further increasing leukocyte recruitment. Polymerase δ-interacting protein 2 (Poldip2) promotes brain vascular inflammation and leukocyte recruitment via unknown mechanisms. This study aimed to define the role of Poldip2 in mediating vascular inflammation and leukocyte recruitment following cerebral ischemia. Cerebral ischemia was induced in Poldip2+/+ and Poldip2+/− mice and brains were isolated and processed for flow cytometry or RT-PCR. Cultured rat brain microvascular endothelial cells were used to investigate the effect of Poldip2 depletion on focal adhesion kinase (FAK)-mediated VCAM-1 induction. Poldip2 depletion in vivo attenuated the infiltration of myeloid cells, inflammatory monocytes/macrophages and decreased the induction of adhesion molecules. Focusing on VCAM-1, we demonstrated mechanistically that FAK activation was a critical intermediary in Poldip2-mediated VCAM-1 induction. In conclusion, Poldip2 is an important mediator of endothelial dysfunction and leukocyte recruitment. Thus, Poldip2 could be a therapeutic target to improve morbidity following ischemic stroke.